Status Gizi Anak Usia 7-12 Tahun Sehubungan dengan Tingkat Pengetahuan Orang Tua - Veronika Vestine; Indah Muflihatin; Gandu Eko Julianto Suyoso; Selvia Juwita Swari; Rossalina Adi Wijayanti; Novita Nuraini (Jurnal Kesehatan, 2021)
Double Burden of Malnutrition is a nutritional problem that is currently facing Indonesia. Parental knowledge is reported as a risk factor that can affect the nutritional status of children. This study was aimed to analyze the relationship between the level of parental knowledge and the nutritional status of children aged 7-12 years. This study was an observational analytic with cross sectional approach. The research was conducted at the Jember Police Primary Clinic during May 2020, with a large sample of 40 parents who have children aged 7-12 years. The results showed that the distribution of respondents who had good knowledge was 70%, sufficient knowledge was 27.5% and less knowledge was 2.5%. The distribution of respondents with under weight status was 7.5%, normal status was 87.5% and over weight status was 5%. The level of knowledge has a significant (p = 0.021), strong (dxy = 0.613) and positive relationship to the nutritional status of children aged 7-12 years. Knowledge of children's growth and nutritional status is very important for parents because it has the potential to influence parents in caring for and caring for their children, especially in meeting nutritional needs. Keywords: Children, Knowledge, Nutritional